Control of Dc Motor External Resistor Starter by Using Armature Current Decay Sensing Technique - Mohd Rusllim, Mohamed (2015)
Advancement of AC motor over last 100 years coupled with regular maintenance requirement of a DC motor has made DC motor become unpopular to be widely used in modern industries. Even so, for industries that require high torque output and variable speed, DC motor is still in demand. Nonetheless, reducing high starting current is a challenge. This paper discusses control strategies for reducing high starting current to a considerable safer value, i.e. up to at most three times of full load torque current. In doing so, a set of external resistance is applied to the armature winding of DC motor and equipped with the automatic control switch. The value of carried load torque determines the execution of control switch, thus resulted in reduction of start-up period with minimum losses and improves the efficiency of forward-reverse control. The results suggested that no ill effect on speed smoothness and torque load carrying capacity during starting time.